Zmiany w praktyce w przedszkolach w Republice Czeskiej - Radmila Burkovičová, Radmila Burkovičová (Studia Edukacyjne, 2020)
Relatively extensive changes are currently taking place in the system of preschool education in the Czech Republic, which will mainly affect the educational landscape of kindergartens. A personalityoriented model of preschool education requires a considerate, understanding and helping approach to each child. The joint education of all children, where inclusion occurs for certain children who were excluded from children’s communities in the past, is happening within the context of Czech and international legislation. Supporting measures are provided to children where required. However, such measures may ultimately also benefit the teacher.